IMPLEMENTASI TQM MELALUI EMPOWERMENT DAN ORGANIZATIONAL COMMITMENT DALAM MENINGKATKAN SEMANGAT KERJA KARYAWAN PADA PT. ADEI PLANTATION & INDUSTRY - Dosmaria Bunga Valensia Hutajulu; Samsir Samsir; Anggia Paramitha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
Total Quality Management is a systematic management approach oriented by organization, costumer and market through combination of practical factfinding and problem solving to create significant improvements in quality, productivity and others. Two of Total Quality Management’s Principles are Empowerment and Organizational Commitment. This study aims to determine the implementation of Total Quality Management (TQM) through Empowerment and Organizational Commitment either simultaneously and partially to spirit work at PT. Adei Plantation & Industry, PMKS-Mandau Duri, Bengkalis District. Population in this study is all employees of factory that work in PT. Adei Plantation & Industry and sample are 52 employees. The research method is to use quantitative descriptive method and multiple linear regression with SPSS version 21.The study results simultaneously (Test F), indicate that all independent variables studied have a significant influence on total quality management spirit work. The influence level of each independent variable to dependent variable can be known by partial test, with R2 value 55,8%. Therefore, Empowerment variable (X1) has significant effect on spirit work (Y) and also Organizational Commitment (X2) and spirit work (Y).Keywords : empowerment, organizational commitment, spirit work